Physical activity adapted to the disabled person: the crossfit adapted as an experience for people with wheelchairs and amputees - Danielle Da Silva Pinheiro Wellichan; Marcella Garcia Ferreira dos Santos (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
The practice of physical activity generally brings numerous health benefits. For people with disabilities, the benefits are even greater in view of the need of each individual in particular. Strength, agility, balance, motor coordination, are some of them, as well as psychological and social aspects, such as improvement in self-esteem, motivation, confidence, health promotion and socialization. Increasingly, adapted sport has been accepted and expanded thanks to the good results achieved and, in this context, some modalities have been good options for people with disabilities. In order to know more about the activity and its benefits as a physical activity, it was verified that the CrossFit Adapted has provided experiences in several aspects, as reported in this text, through interviews with a practicing group. It is hoped that this modality will gain visibility and that new units of the modality will be created by the country to extend the experience to other people.